2023
DOI: 10.1021/acssuschemeng.2c05676
|View full text |Cite
|
Sign up to set email alerts
|

Green Electrospinning of Biodegradable Cellulose Acetate Nanofibrous Membranes with Tunable Porosity

Abstract: The electrospinning of polymer nanofibers has received significant attention owing to their high surface-area-tovolume ratio, high porosity, adjustable pore size and texture, and highly interconnected porous structure. In particular, the electrospinning of biodegradable cellulose acetate (CA) nanofibers has sparked interest in diverse applications, including drug delivery systems, scaffolding for tissue engineering, air filtration, and affinity membrane systems. However, the electrospinning process has been mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Consequently, there exists a necessity to transition membrane production techniques towards environmentally sustainable alternatives, characterised by reduced utilization of hazardous solvents and adherence to principles of sustainability. [51][52][53][54][55] Furthermore, in order to optimize the effectiveness of the separation process, a range of modifications and manufacturing techniques have been employed with regard to the membrane. Significant enhancements in membrane performance have been achieved by modifying surface properties using various techniques, including plasma etching, 56 thermal crosslinking, 57 and oxidation.…”
Section: Membrane Technology For Water Treatment and Its Market And U...mentioning
confidence: 99%
“…Consequently, there exists a necessity to transition membrane production techniques towards environmentally sustainable alternatives, characterised by reduced utilization of hazardous solvents and adherence to principles of sustainability. [51][52][53][54][55] Furthermore, in order to optimize the effectiveness of the separation process, a range of modifications and manufacturing techniques have been employed with regard to the membrane. Significant enhancements in membrane performance have been achieved by modifying surface properties using various techniques, including plasma etching, 56 thermal crosslinking, 57 and oxidation.…”
Section: Membrane Technology For Water Treatment and Its Market And U...mentioning
confidence: 99%
“…(h) SEM image showing the bacteria growth on PLA surface after 20 days of treatment in cow-dung, jaggery and water containing biodegradation slurry; adapted with permission from [ 173 ]. Biodegradability tests performed on the CA electrospun based membranes by employing esterase and cellulase enzymes: (i) Polypropylene fibrous membrane used as control, given its non-susceptibility to degrade under enzymes conditions; (j) CA nanofibers tissue; (k) CA nanofibers tissue processed with tetrabutylammonium bromide (TBAB); and (l) CA nanofibers tissue processed with High-foaming HoneySurf (HS); adapted with permission from [ 204 ]. …”
Section: The Use Of Electrospun Nanofibers In Surgical Mask and Respi...mentioning
confidence: 99%
“…Also, Oldal et al. observed that CA electrospun nanofibers membrane can be easily degraded by means of natural enzymes, such as cellulase and esterase [ 204 ]. Compared to pristine CA nanofibers, a faster response in the degradation process has been observed for CA membranes pretreated in solution with green surfactant ( Fig.…”
Section: The Use Of Electrospun Nanofibers In Surgical Mask and Respi...mentioning
confidence: 99%
“…7,10,13 Several strategies have been implemented to overcome these challenges, including physical and chemical modification 13−15 and the use of harsh and hazardous solvents. 16,17 A versatile approach involves fabricating multicomponent constructs which can help avoid the use of toxic reagents as solvents, cross-linkers, or processing aids. 7 Moreover, the integration of constituents with complementary properties into a single fabric can provide multifunctionality to the hybrid materials.…”
Section: Introductionmentioning
confidence: 99%